The growing intergenerational divide in Europe - Pia Hüttl; Karen Wilson; Guntram B. Wolff (Bruegel, 2015)
During the economic and financial crisis, the divide between young and old in the European Union increased in terms of economic well-being and allocation of resources by governments. As youth unemployment and youth poverty rates increased, government spending shifted away from education, families and children towards pensioners. To address the sustainability of pension systems, some countries implemented pension reforms. We analysed changes to benefit ratios, meaning the ratio of the income of pensioners to the income of the active working population, and found that reforms often favoured current over future pensioners, increasing the intergenerational divide. We recommend reforms in three areas to address the intergenerational divide: improving European macroeconomic management, restoring fairness in government spending so the young are not disadvantaged, and pension reforms that share the burden fairly between generations.
Keywords: 330